Blended Learning as a Guarantee of Increasing the Literacy of Students in the Lessons of Russian as a Foreign Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Blended learning technology is one of the most promising. This article discusses the possibility of using a blended learning model in the lessons of Russian as a foreign language based on the creative approach of teachers in higher educational institutions of Uzbekistan. This can be achieved, in our opinion, by being fluent in languages, in our time especially Russian. If in the previous decades of the twentieth century the circle of people who had the need to communicate in Russian was quite narrow, then at present the situation has changed.